Inteligencia emocional y desempeño laboral en la Municipalidad Provincial de Ucayali Contamana 2024 - Huaman Flores, Italo (2025)
The general objective of the thesis was to determine the relationship between emotional intelligence and work performance in the Provincial Municipality of Ucayali Contamana 2024. The research was of a basic type, with a non experimental design and a correlational approach. We worked with a sample of 85 selected workers, who answered questionnaires designed to evaluate both variables. The results revealed that the predominant level of emotional intelligence in workers is "regular" (23%), reflecting a moderate ability to manage and understand emotions in the work environment. Similarly, job performance was also mostly at a "fair" level, indicating that while employees meet basic performance standards, there is considerable scope to improve their performance. The statistical analysis showed a Pearson correlation coefficient of 0.736, which shows a strong positive correlation between emotional intelligence and job performance. This finding suggests that as workers improve their ability to manage emotions, they also increase their work performance. In addition, this result was statistically significant, with a significance level of 0.000, confirming the validity of the findings. In conclusion, strengthening emotional intelligence can be a key strategy to improve work performance in the Provincial Municipality.